Urgensi Pendidikan Kesehatan Mental secara Islami pada Remaja di Era Digital - Asriyanti Rosmalina (UIN Siber Syekh Nurjati Cirebon, 2024)
The development of the times in the current digital era, has a positive and negative impact on the stages of adolescent development. Among the development of mental health for adolescents as an individual, the category of child development in the final phase shows that their development still requires self-control guidelines for thinking and acting. to develop the health potential of adolescents can be done with Islamic mental health education which becomes a process of building awareness and concern for all people with prevention efforts based on early detection, promotive carried out through the process of socialization and increasing Islamic worship. The research method used is a type of library research or (library research). Based on the results of library research, it shows that teenagers who understand religious guidelines and carry out these understandings in everyday life such as praying, remembrance, reading the Qur'an as well as good motivational support from parents also make teenagers more able to easily socialize with the environment, able to control emotions in a variety of effective ways and increased concern for others.